Determinants of Digital Market Expansion Among Fisheries-Based Small Enterprises - Muhammad Arifin; Hamdan Zaenuri (Journal of Community Action, 2026)
This study examines the determinants of digital market expansion among fisheries-based small enterprises. It focuses on how technological, organizational, socio-economic, and policy-related factors influence market access, competitiveness, and business sustainability in the digital economy. The research employs a systematic literature review of 30 peer-reviewed articles and indexed repositories covering fisheries MSMEs, digital transformation, and e-commerce adoption. The findings indicate that technological factors such as e-commerce platforms, social media utilization, search engine optimization, and digital advertising significantly enhance market visibility and consumer engagement. Organizational factors, including branding, packaging innovation, managerial capability, and financial literacy, strengthen firms’ ability to implement digital strategies effectively. Socio-economic conditions, particularly digital literacy, education level, and income status, determine the degree of technology adoption among fisheries-based enterprises. Policy-related factors, including government subsidies, training programs, institutional support, and infrastructure availability, play a critical role in enabling digital inclusion and reducing adoption barriers. The study concludes that digital market expansion is a multi-dimensional process that requires an integrated ecosystem approach. Technology adoption alone is insufficient without supporting organizational capacity, socio-economic empowerment, and institutional backing. Strengthening these interconnected determinants is essential to enhance competitiveness and ensure sustainable market growth for fisheries-based small enterprises.